Rational design of nitrogen and fluorine co-doped metal-free porous carbons electrocatalysts for highly efficient oxygen reduction and zinc-air batteries - Linqiang Li; Na Qin; Huayun Ma; Jing Liu; Zhiqiang Zhu; Yaxiong Huo; Lipeng Zhai; Liwei Mi (Carbon Neutrality)
Abstract The oxygen reduction reaction (ORR) is an important reaction in fuel cells and metal air batteries. The reaction is affected by slow kinetics and the use of high-priced and resource-scarce platinum-based catalysts. Therefore, there is an urgent need to develop cost-effective nonprecious metal catalysts for use in the ORR to replace Pt-based catalysts. In this study, we used two-dimensional covalent organic frameworks (recorded as TF-COFs) as precursors to produce a metal-free nitrogen and fluorine-co-doped porous carbon catalyst (recorded as TF-800, TF-900, TF-1000, and TF-1100). TF-1000 had a high initial potential (0.90 V) and half-wave potential (0.83 V) in an alkaline medium, indicating good catalytic activity. In addition, the ORR stability of TF-1000 was better than that of commercial Pt/C (20%). This is mainly because the porous carbon catalyst has a high specific surface area, and the nitrogen and fluorine atoms in it have good dispersion and synergistic effects on the polarization of adjacent carbon atoms. TF-1000 also shows excellent performance in zinc-air batteries. In the TF-1000 based zinc-air batteries, excellent battery performance was observed: the peak power density reached 216.66 mW·cm–2, the specific capacity reached 752.86 mAh·g–1 at 10 mA·cm–2, and the long-term charge–discharge stability was demonstrated. This work provides inspiration for new strategies to prepare future ORR catalysts.